Fire safety of a novel concept of ventilated façade integrating Phase Change Materials - Ovadiuc Emanuil-Petru; Calotă Răzvan; Năstase Ilinca; Simion Adrian; Anghel Ion (E3S Web of Conferences)
Ventilated facades represent a modern solution increasingly adopted in smart, low-energy building designs. A critical consideration in the implementation of these systems is ensuring fire resistance while simultaneously minimizing the risk of fire propagation. Modern ventilated facade solutions incorporate solar energy storage using phase change materials (PCMs). This study explores the fire performance of storage mass composed of spheres integrating paraffin-based phase-change materials combined with AlO nanomaterials in order to enhance thermal conductivity (nePCM). The investigation focuses on the behavior of these composite materials under fire conditions, providing insights into their safety and efficacy in sustainable building applications.